Aspects of the history of copper mining in Namaqualand - Smalberger, John M (Department of Historical Studies, 2016)
In undertaking this work, the object has been to present a picture of Namaqualand and its mines. This picture is by no means complete, but it is hoped that the pages which follow will in a small way contribute something to the history of Namaqualand. The first chapter deals with the early explorations. Not all of the early travellers to Namaqualand have been mentioned, since not all have had anything of significance to say on the development of the copper mines. Nothing is said of Le Vaillant and John Barrow, to name but two. What we have attempted to show is that, from the very earliest times of European settlement at the Cape, the existence of copper in Namaqualand was known, but that the difficulties of transport prohibited the development of these mines. The second chapter deals with the story of the South African Mining Company. This company was the first mining concern actually to commence operations in Namaqualand, and the first public mining company in South African history. It is for these reasons that its development has been dealt with so extensively. The third chapter deals with the copper mining mania of the 1850's. All too often, the very existence of such a boom is forgotten. Its importance lies in the fact that it was the first purely speculative boom of any extent in the history of South Africa. It marked South Africa's emergence into one of the typical features of a modern economy. The fourth chapter is concerned with the question of leases. The reason for devoting special attention to this is that the final settlement of the lease questions involving the vesting of mineral rights to the mission ground in the state, has been a factor contributing to the present state of conditions existing in these stations. It is a matter of interest, but also of regret, that the development of Namaqualand's mineral wealth was in many respects disastrous for the original inhabitants of the territory. The fifth chapter deals with the transport problem from 1852 until 1876, when the Cape Copper Mining Company constructed its railway. Transport was, and still is, the most important obstacle to the exploitation of Namaqualand's mineral wealth. The first part of the sixth chapter deals with the development of the industry from the commencement of the Cape Copper Company's railway, until 1937, when the O'okiep Copper Company commenced operations. This is rather a long period, and one about which not much is known. An absence of company records has made this section rather impressionistic. The second part of this chapter deals with the history of the O'okiep Copper Company, a company which is still in existence, and which has at present production rates, a life of some ten years. Like its predecessors, the Cape Copper Company and the Namaqua Copper Company, a foreign based organization, its role in the development of Namaqualand is uncertain.